RoboSTEAM - a challenge based learning approach for integrating STEAM and develop computational thinking - Camino, Miguel (2020)
We live in a digital society that needs new better prepared professionals for the new challenges and opportunities provided by the ICT. Students must learn how to deal with all the issues that emerge in this new context. They should acquire computational thinking skills by integrating STEAM, however this needs for changes in current learning curricula and also new learning approaches. RoboSTEAM project deals with this issue by the application of a Challenge Based Learning approach that uses Robotics and Physical Devices. One of the problems found during the project is the complexity of the application of a Challenge Based Learning approach due to the special needs of each educational institution. Given this situation the present work presents provides a flexible definition of challenge and describes also samples regarding how to use them.